Services policy reform and economic growth in transition economies, 1990-2004 - Eschenbach, Felix (Policy research working paper, 2005)
"Major changes have occurred in the structure of former centrally planned economies, including a sharp rise in the share of services in GDP, employment, and international transactions. However, large differences exist across transition economies with respect to services intensity and services policy reforms. The authors find that reforms in policies toward financial and infrastructure services, including telecommunications, power, and transport, are highly correlated with inward foreign direct investment. Controlling for regressors commonly used in the growth literature, they find that measures of services policy reform are statistically significant explanatory variables for the post-1990 economic performance of transition economies. These findings suggest services policies should be considered more generally in empirical analyses of economic growth "--World Bank web site